2013
DOI: 10.1002/jssc.201200683
|View full text |Cite
|
Sign up to set email alerts
|

Ability to determine the desferrioxamine‐chelatable iron fractions of nontransferrin‐bound iron using HPLC

Abstract: Iron is an essential element in human development. It is imperative for oxygen and electron transport and also for DNA and neurotransmitters synthesis. On the other hand, this metal is able to participate in Fenton's reaction that in turn leads to free radical damage. The most toxic fraction of iron - nontransferrin-bound iron and its part desferrioxamine-chelatable iron - can serve as an exquisite biomarker in the identification of iron imbalance. The goal of the present study was to devise a simple, repeatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This assay as implemented also demonstrated the greatest assay dynamic range (∼50 μM to at least 2 mM) of the assays tested in this study. The assay was not optimized in this work to minimize the LOD given that the labile iron of the agent samples in this study were in the hundreds of μM range; indeed a sub‐μM LOD has been reported for a similarly implemented assay showing further improvement in LOD may be possible . However, the LOD was routinely achievable and more than sufficient for the scope of work described.…”
Section: Resultsmentioning
confidence: 99%
“…This assay as implemented also demonstrated the greatest assay dynamic range (∼50 μM to at least 2 mM) of the assays tested in this study. The assay was not optimized in this work to minimize the LOD given that the labile iron of the agent samples in this study were in the hundreds of μM range; indeed a sub‐μM LOD has been reported for a similarly implemented assay showing further improvement in LOD may be possible . However, the LOD was routinely achievable and more than sufficient for the scope of work described.…”
Section: Resultsmentioning
confidence: 99%
“…Various techniques have been used for the determination of deferoxamine include spectrophotometry 6 , 7 HPLC 8,9 .…”
Section: Research Articlementioning
confidence: 99%
“…the quantitative measurement was performed using the RP-hPlc method. chromatographic separation was performed by gradient elution using a cadenza cD-c18 column with solvent 10 mM tris-hcl and solvent acetonitrile-acN on the basis of a previously reported study by Koba et al [3]. the step-form gradient elution conditions were optimised experimentally with a total run time of 15 min and with gradient changes in time of the hPlc analysis as follows: 15% during 0-1 min, 45% during 1-5 min, and 15% during 5-15 min.…”
Section: Preparation Of Calibration Curvementioning
confidence: 99%
“…the damaging effect of NtBi is associated with its ability to take part in the Fenton reaction, which may result, among others, in cellular membrane damage and induce apoptosis [3]. Previous studies have reported that NtBi is not detected in the serum of the healthy population [4,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation